Investigation of Behavioral Dysfunctions Induced by Monoamine Depletions in a Mouse Model of Parkinson's Disease - Li, Yong; Jiao, Qian; Du, Xixun; Bi, Mingxia; Han, Shuaishuai; Jiao, Lingling; Jiang, Hong (Frontiers in Cellular Neuroscience, 2018)
Parkinson’s disease (PD) is characterized not only by typical motor symptoms, but also by nonmotor symptoms in the early stages. In addition to the loss of dopaminergic (DAergic) neurons, progressive degenerations of noradrenergic (NA) and serotonergic (5-HT) neurons were also observed. However, the respective effects and interactions of these monoamine depletions on certain nonmotor symptoms are still largely unknown. In the present study, we performed selective depletions of NA, 5-HT and DA in mice by intraperitioneal injection of N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine hydrochloride (DSP-4), 4-chloro-L-phenylalanine (pCPA) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), respectively. DSP-4 led to a 34% decrease in the number of NAergic neurons in the locus coeruleus, and MPTP led to a 30% decrease in the number of DAergic neurons in the substantia nigra. Although there was no obvious change in the number of 5-HTergic neurons in the dorsal raphe nucleus after pCPA treatment, the levels of 5-HT and its metabolite in the frontal cortex and hippocampus were reduced, respectively. Locomotor activity deficit was induced by DA depletion and a decrease in traveled distance was potentiated by additional NA depletion. Despair-associated depressive-like behavior could be observed in every group. Anxiety states emerged only from the combined depletion of two or three monoamines. However, combined depletion of the three monoamines dramatically induced anhedonia, and it could also aggravate the depressive-like and anxiety behavior. Furthermore, NA depletion significantly reduced spatial learning and memory ability, which was not enhanced by additional 5-HT or DA depletion. Our data highlighted the interactive role of NA, 5-HT and DA in the motor, emotional and cognitive deficits, providing new insight into the complex orchestration of impaired monoaminergic systems that related to the pathology of PD.